1997
DOI: 10.1046/j.1365-2559.1997.5370782.x
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomesotheliomatous angiosarcoma: a pleuropulmonary lesion simulating malignant pleural mesothelioma

Abstract: We report two cases of autopsy confirmed angiosarcoma in adult males, presenting as diffuse pleuropulmonary tumours and simulating malignant mesothelioma. Both the lesions grew along the serosal surfaces and were characterized by variably thick rinds of tissue encasing the lung. The pulmonary parenchyma showed diffuse, dark red, subpleural consolidations and multiple cavitations. Histologically, the lesions were composed by atypical spindle and polygonal, epithelioid cells showing rudimentary vascular differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 10 publications
1
30
0
Order By: Relevance
“…The two sarcomas with the greatest potential of being confused with pleomorphic mesotheliomas are angiosarcomas and the pleomorphic variant of malignant fibrous histiocytoma. Pleural angiosarcomas are often epithelioid and can easily be mistaken for a mesothelioma, both clinically and histologically, [27][28][29][30] and examples of epithelioid pleural angiosarcomas exhibiting marked pleomorphism that could easily be confused with pleomorphic mesotheliomas have been documented in the literature. 31 The pleural biopsy of one of the mesotheliomas cases in this study (case 1), in addition to being somewhat hemorrhagic, showed areas in which the neoplastic cells appeared to be lining irregular spaces resembling the vascular spaces seen in an angiosarcoma ( Figure 1a).…”
Section: Discussionmentioning
confidence: 99%
“…The two sarcomas with the greatest potential of being confused with pleomorphic mesotheliomas are angiosarcomas and the pleomorphic variant of malignant fibrous histiocytoma. Pleural angiosarcomas are often epithelioid and can easily be mistaken for a mesothelioma, both clinically and histologically, [27][28][29][30] and examples of epithelioid pleural angiosarcomas exhibiting marked pleomorphism that could easily be confused with pleomorphic mesotheliomas have been documented in the literature. 31 The pleural biopsy of one of the mesotheliomas cases in this study (case 1), in addition to being somewhat hemorrhagic, showed areas in which the neoplastic cells appeared to be lining irregular spaces resembling the vascular spaces seen in an angiosarcoma ( Figure 1a).…”
Section: Discussionmentioning
confidence: 99%
“…These include epithelioid mesotheliomas, AdCAs, epithelioid nerve sheath tumors, melanomas, and pseudomesotheliomatous angiosarcomas. 45 By far, the most common tumors in this category are AdCA and mesothelioma. Therefore, our study focused on the most common differential diagnostic issue in this setting, namely, the distinction between epithelioid mesothelioma and AdCA involving serous surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Pleural angiosarcomas are often epithelioid (74%) (10) and can be easily mistaken for mesothelioma or carcinoma both clinically and histologically (1,2,8). In our case, focal histologic findings suggested an involvement of carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these serous membrane-related angiosarcomas show histologically epithelioid feature, and the distinction from other common tumors such as mesothelioma and metastatic carcinoma is difficult (1,2). A total of 31 cases of primary malignant pleural vascular tumors were identified in the English literature (1)(2)(3)(4)(5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%